UPAYA MENINGKATKAN KETERAMPILAN PROSES SAINS DAN MENGURANGI MISKONSEPSI MELALUI PENERAPAN E-MODULE BERBASIS PROBLEM-BASED LEARNING KELAS X MIA 2 SMA BATIK 1 SURAKARTA - Henny Purnama Wati; Puguh Karyanto; Sri Dwiastuti; Dynna Sri Wulandari (BIO-PEDAGOGI, 2016)
This research aimed to improve the scientific process skills and reduce misconception through the application of E-Module based on Problem-Based Learning in the X MIA 2 graders of SMA Batik 1 Surakarta. This research was a Classroom Action Research consisting of 2 cycles. Each cycle consisted of four stages: planning, acting, observing, and reflecting. The subject of research was the X MIA 2 graders of SMA Batik 1 Surakarta consisting of 42 students. Techniques of collecting data used were multiple choice test and observation to measured scientific process skills, open-ended reasoning of Two-Tier Diagnostic Test to measure misconseption, and interveiw as the proponent data related learning process. The data were analyzed using descriptive qualitative technique consist of three component: data reduction, data presentation, and taking the conclusion. Data validation was carried out using triangulation method. Target of research was 20% to increased scientific process skills and 20%  to reduced misconseption at the end of the cycle. The result of research showed that the scientific process skills to able increased through the application of E-Module based on Problem-Based Learning in all aspects: observing of 29.83%, categorizing of 11.73%, predicting of 37.33%, interpreting of 30.71%, measuring of 35.66%, communicating of 32.39%, designing experiment of 30.04%, experimenting of 21.82%, asking question of 23.42%, hypothesizing of 36.73%, and applying concept of 42.58%. On the other side, the  result of research also showed that there was a decreased misconception in ecological concept: population of 51.31%, community of 43.73%, ecosystem of 39.36%, and science, environment, technology and community (salingtemas) ecology of 54.33%. The conclusion of this research described that there was an increasing scientific process skills of 28.96% and reducing misconception of 47.18% by used the application of E-Module based on Problem-Based Learning. Keywords  : Scientific Process Skills, Misconception, E-Module based on Problem Based Learning.